2016
DOI: 10.1680/jadcr.15.00103
|View full text |Cite
|
Sign up to set email alerts
|

The influence of physico-chemical properties of fly ash and CKD on strength generation of high-volume fly ash concrete

Abstract: This paper presents a laboratory study on the use of Cement Kiln Dust (CKD) as an activator of fly ash when used in high volumes within concrete. Two separate batches of fly ash and CKD were tested to assess the effect of material variability on binder properties and compressive strength gain. Ternary blends of fly ash (55% -65%), CEM 1 (30%) and CKD (5% -15%) and quaternary blends that included moderate amounts (15% -18.5%) of Ground Granulated Blast-Furnace Slag (GGBS) were prepared.Physico-chemical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The BM3 sample achieved the highest value of compressive strength, where the main binder constituents in the mixture (clinker, limestone, and GGBS) were at the minimum level of the recommended range for the DoroCem product. High compressive strength values (60–69 MPa) of quaternary mixes consisting of 30 wt.% Portland cement, 45–50 wt.% fly ash, 5–10 wt.% BPD, and 15–18.5 wt.% GGBS after 28 days of hardening were achieved [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The BM3 sample achieved the highest value of compressive strength, where the main binder constituents in the mixture (clinker, limestone, and GGBS) were at the minimum level of the recommended range for the DoroCem product. High compressive strength values (60–69 MPa) of quaternary mixes consisting of 30 wt.% Portland cement, 45–50 wt.% fly ash, 5–10 wt.% BPD, and 15–18.5 wt.% GGBS after 28 days of hardening were achieved [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Better results were achieved when CKD was used in the concretes with pozzolanic additives, slag cement or special sulfate-resistant cement. Many authors [36,37] have observed enhanced flexural splitting, splitting tensile and compressive strengths with the simultaneous use of an optimal amount of CKD (up to 10%) as well as fly ash and granulated blast furnace slag and as additives. The important role of CKD in activating the properties of pozzolanic additives during cement hydration as well as the increase in ettringite volume was found.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high alkalinity and significant metal content, CCR seriously harms the environment 31 . The high alkalinity of CCR makes it appropriate for activating GGBFS, thereby enhancing its reactivity during the early stages 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%